Hedgehog Signal and Genetic Disorders - Sasai, Noriaki; Toriyama, Michinori; Kondo, Toru (Frontiers in Genetics, 2019)
The hedgehog (Hh) family comprises sonic hedgehog (Shh), Indian hedgehog (Ihh), and desert hedgehog (Dhh), which are versatile signaling molecules involved in a wide spectrum of biological events including cell differentiation, proliferation, and survival; establishment of the vertebrate body plan; and aging. These molecules play critical roles from embryogenesis to adult stages; therefore, alterations such as abnormal expression or mutations of the genes involved and their downstream factors cause a variety of genetic disorders at different stages. The Hh family involves many signaling mediators and functions through complex mechanisms, and achieving a comprehensive understanding of the entire signaling system is challenging. This review discusses the signaling mediators of the Hh pathway and their functions at the cellular and organismal levels. We first focus on the roles of Hh signaling mediators in signal transduction at the cellular level and the networks formed by these factors. Then, we analyze the spatio-temporal pattern of expression of Hh pathway molecules in tissues and organs, and describe the phenotypes of mutant mice. Finally, we discuss the genetic disorders caused by malfunction of Hh signaling-related molecules in humans.